2024
DOI: 10.1038/s41467-024-45190-6
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic computer-to-brain communication enhancing naturalistic touch sensations via peripheral nerve stimulation

Giacomo Valle,
Natalija Katic Secerovic,
Dominic Eggemann
et al.

Abstract: Artificial communication with the brain through peripheral nerve stimulation shows promising results in individuals with sensorimotor deficits. However, these efforts lack an intuitive and natural sensory experience. In this study, we design and test a biomimetic neurostimulation framework inspired by nature, capable of “writing” physiologically plausible information back into the peripheral nervous system. Starting from an in-silico model of mechanoreceptors, we develop biomimetic stimulation policies. We the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 104 publications
0
1
0
Order By: Relevance
“…It was observed that, to some extent, biomimetic neurostimulation could promote mobility (primary outcome) and reduce mental effort (secondary outcome) compared to traditional approaches. The outcomes of this neuroscience-driven technology, inspired by the human body, may serve as a model for advancing assistive neurotechnologies 186 (as shown in Fig. 17f).…”
Section: Latest Achievementsmentioning
confidence: 99%
“…It was observed that, to some extent, biomimetic neurostimulation could promote mobility (primary outcome) and reduce mental effort (secondary outcome) compared to traditional approaches. The outcomes of this neuroscience-driven technology, inspired by the human body, may serve as a model for advancing assistive neurotechnologies 186 (as shown in Fig. 17f).…”
Section: Latest Achievementsmentioning
confidence: 99%